Implementation of Electronic Reporting in Peruvian Public Administration - Segura, Aldo Elliot (2015)
The new information and communication technologies allow their benefits are applied for the improvement of governance, this can be pleasantly translate in the administrative simplification of administrative processes, a situation that with something as important as giving formality to the electronic notification can result in tangible benefits for the administered and the State itself.Currently prevailing ideas that underlie the use of these technologies in the legal field, although his adaptation comes to forced march but there is no doubt that this is the future that awaits us.